Circular - Schevenels, Walther, b. 1894
029-0110-001 FÉDÉRATION SYNDICALE INTERNATIONALE INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONALER GEWERKSCHAFTSBUND 9, AVENUE D'ORSAY, PARIS - VIIe ADRESSE TÉLÉGRAPHIQUE: TELEGRAPHIC ADDRESS: INTERFED, PARIS TELEPHONE: INVALIDES 45-88 TELEGRAMMADRESSE: Sch/H/B. F.I.S. 762 19th July, 1937 To Affiliated National Centres To Relief Committees for Spain Dear Comrades, In order that we may bring our statistics up to date, we should be much obliged if you would let us have the exact figures for the subscriptions and collections made up till now for Spain, including therein the amounts sent to the International Solidarity Fund and the sums utilised in your own country for the purchase and despatch of goods to Spain, or for the accomodation of Spanish refugees and women and children who have been evacuated. We should be glad if you would also include in this list the gifts in kind, either despatched to Spain or distributed in your country for the refugees. An estimate, even an approximate one, should be made of the value of such gifts, and this included in the statement. Looking forward to your reply, Yours sincerely. W. Schevenels General Secretary 292/946/29/110